2011
DOI: 10.1038/nchembio.664
|View full text |Cite
|
Sign up to set email alerts
|

On-resin N-methylation of cyclic peptides for discovery of orally bioavailable scaffolds

Abstract: Backbone N-methylation is common among peptide natural products and has a significant impact on both the physical properties and the conformational states of cyclic peptides. However, the specific impact of N-methylation on passive membrane diffusion in cyclic peptides has not been investigated systematically. Here we report a method for the selective, on-resin N-methylation of cyclic peptides to generate compounds with drug-like membrane permeability and oral bioavailability. The selectivity and degree of N-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
309
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 330 publications
(332 citation statements)
references
References 31 publications
9
309
0
4
Order By: Relevance
“…Group 1 contains cyclic hexapeptides with the general sequence, cyclo(Leu-Leu-Leu-Leu-Pro-Tyr), but have varied chirality and N-methylation configurations, and therefore are expected to have varied conformations. Some of these peptides have been reported to have high in vitro and in vivo permeability; peptides 12 (referred to as 1 in [14]) and 13 (referred to as 15 in [15]), for example, both displayed oral bioavailability greater than 20%, which is unusually high for peptides. Group 2 comprises peptides with a similar range of chirality and N-methylation configurations as those in Group 1, but was designed to explore the effect of sequence variation on peptide permeability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Group 1 contains cyclic hexapeptides with the general sequence, cyclo(Leu-Leu-Leu-Leu-Pro-Tyr), but have varied chirality and N-methylation configurations, and therefore are expected to have varied conformations. Some of these peptides have been reported to have high in vitro and in vivo permeability; peptides 12 (referred to as 1 in [14]) and 13 (referred to as 15 in [15]), for example, both displayed oral bioavailability greater than 20%, which is unusually high for peptides. Group 2 comprises peptides with a similar range of chirality and N-methylation configurations as those in Group 1, but was designed to explore the effect of sequence variation on peptide permeability.…”
Section: Resultsmentioning
confidence: 99%
“…Looking beyond lipohilicity, we then considered the hydrogen bonding potential of the peptides following recent literature reports on the importance of intra-molecular and intermolecular hydrogen bonds for cyclic peptides [14][15][16] and small molecules [38]. Specifically, structural studies of cell-permeable peptides have suggested that steric occlusion of polar groups and internal hydrogen bonding can lead to increased permeability [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Membrane permeability is often used to predict whether a compound will be orally absorbed since the first barrier after surviving the GI tract is membrane permeation and resistance to enterocyte metabolism. 22−25 In the RRCK assay, compound 1 had lower permeability (P app = 1.7 × 10 −6 cm·s −1 ) than CSA (P app = 5 × 10 −6 cm·s −1 ), 12 while cyclic hexapeptide isomers 2 and 3 had 6−7-fold greater permeability than 1 and 2−3-fold higher RRCK permeability than CSA ( Figure 1A).…”
mentioning
confidence: 99%
“…The drug-like properties of cyclic peptides arise from their constrained rigid structure, improved bioavailability, membrane permeability relative to linear peptides, and resistance to degradation by host proteases (2)(3)(4). Organic synthesis of large peptide libraries is constrained by practical concerns, thereby limiting the diversity of sequence variants that would be necessary to truly explore scaffold space.…”
mentioning
confidence: 99%